Inadequate iodine status among women of childbearing age in Northern Norway: a cross-sectional study - Maren Johnsen; Guri Skeie; Tonje Braaten; Marianne Hope Abel; Sandra Huber; Marian Kjellevold; Elin Evensen; Margaret Rayman; Solrunn Hansen (Food & Nutrition Research)
Background: Iodine is crucial for thyroid hormones, normal metabolism, growth and development in the foetal period. Low iodine status in women of childbearing age is particularly worrying since iodine deficiency continues into pregnancy. Objective: This study aimed to measure iodine status in non-pregnant and pregnant women in Northern Norway and investigate group differences and determinants of urine iodine concentrations (UICs) based on dietary factors and participants’ knowledge about iodine. Methods: This cross-sectional study included pregnant (n = 131) and non-pregnant (n = 493) women from the Northern Norway Mother-and-Child Contaminant Cohort Study 2 study (2017–2021) and the Fit Futures 3 study (2020–2021). UIC was measured in spot urine, and dietary iodine intake was calculated from food frequency questionnaires. Group differences in median UIC were explored using non-parametric tests. Associations between independent variables and median UIC were estimated through quantile regression, adjusting for relevant covariates. Results: Median UIC was 91 μg/L in non-pregnant and 134 μg/L in pregnant women, thus below the World Health Organization definition of insufficient iodine status of < 100 μg/L and 150 μg/L, respectively. Dairy products and lean fish were the most important dietary iodine sources, but the median estimated intake did not reach the recommended intake. Taking iodine supplements was the strongest determinant of UIC in both groups (P < 0.01), and users had adequate iodine status at a group level. A high proportion of the non-pregnant women (84%) were not taking iodine supplements. Poor knowledge about iodine in the participant groups was observed but was not associated with UIC. Conclusion: Pregnant and non-pregnant women not using iodine supplements had inadequate iodine status and insufficient iodine intake. Supplement use or interventions at the societal level are essential to ensure adequate status in these vulnerable groups.